Dynastic inequality compared: Multigenerational mobility in the US, the UK, and Germany - Guido Neidhöfer; Maximilian Stockhausen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Using harmonized household survey data, we analyse long run social mobility in the US, the UK, and Germany and test recent theories of multigenerational persistence of socio-economic status. In this country comparison setting we find evidence against Gregory Clark's "universal law of social mobility". In general, our results show that the long run persistence of socio-economic status tends to vary with the institutional context. Our findings on the existence of a direct and independent effect of grandparents' social status on grandchildren's status are mixed.
Keywords: D63; I24; J62; 330; dynastic inequality; intergenerational mobility; multigenerational persistence; three generations; grandparental effect